Fragment screening against Schistosoma mansoni dihydroorotate dehydrogenase: a modern approach for drug discovery - Mori, Renan Minin de (2021)
Prevalent in tropical and subtropical areas, schistosomiasis is a serious public health problem, especially in rural and poor communities without access to adequate sanitation and safe drinking water, being one of the most prevalent neglected tropical diseases (NTDs). Transmission has been reported in dozens of countries with 52 considered endemic regions. Its control, over the past 30 years, depends on a single drug, praziquantel. Its mechanism of action is not fully understood and displays considerable drawbacks. Therefore, the development of an alternative treatment for schistosomiasis is unquestionably urgent. In the last decades, due to the advance of recombinant DNA and gene technologies, the use of target-based drug discovery (TDD) has increased significantly. Our work has focused on exploiting TDD strategies to develop new therapeutics to treat schistosomiasis, mainly based on the use of fragment screening. By using compounds of low molecular weight, fragment screening has appeared as an important strategy in the pipeline of drug discovery. Fragments can cover a broader range of the chemical space with fewer compounds, often binding with better ligand efficiencies than traditional screening. With this, hits are generally able of binding to a higher number of proteins than conventional \'drug-size\' molecules. We were interested in evaluating the enzyme dihydroorotate dehydrogenase (DHODH) as a drug target against schistosomiasis DHODH is a flavoenzyme that catalyzes the stereospecific oxidation of (S)-dihydroorotate (DHO) to orotate during the fourth and only redox step of the de novo pyrimidine nucleotide biosynthetic pathway, laying at the center of critical biochemical pathways. DHODH has been considered an important drug target for cancer, autoimmune and parasitic diseases, among other infections. In collaboration with Prof. Flávio Emery\'s laboratory, we screened several fragments against the Schistosoma mansoni DHODH (SmDHODH) through the use of structural, biophysical, and enzymatic assays, and identified potent and selective inhibitors against SmDHODH in the nanomolar range. We also reported here the first crystal structure of SmDHODH in complex with an atovaquone analogue inhibitor (PDB: 6UY4). Our structural studies have shown: (a) the open conformation of the active site loop in a class 2 DHODH; (b) the presence of a protuberant domain, only noticed for Schistosoma spp. DHODHs, that could modulate and control the inhibitor binding site; (c) a detailed description of an unexpected binding mode for the atovaquone analogue to SmDHODH. With this, our work reveals key molecular interactions required for the activity of atovaquone and its analogues, and presents the basis for fragments optimization that could guide future drug design strategies in the fight against schistosomiasis.